Bioplastic from mango leaves / Hariz Erzam, Muhammad Khairul Arrifin and Siti Salwa Abdul Aziz - Erzam, Hariz; Arrifin, Muhammad Khairul; Abdul Aziz, Siti Salwa (2020)
Plastic is a synthetic material made from a wide range of organic polymers such as polyethylene, PVC, nylon, and others. It can be moulded into shape while soft, and then set into a rigid or slightly elastic form. In Malaysia, it is generally used for food packaging, toys furniture and other applications. Even though it is very convenient, plastics derived from petroleum are not biodegradable. More than 80 million tonnes of plastic enters the world's oceans each year. Meanwhile, bioplastic is a type of biodegradable plastic derived from biological substances rather than petroleum. The demand for bioplastic is increasing along with the rising concern towards environmental problems caused by petroleum-based plastic. Global production capacity of bioplastic increased by 68% per year during 2003 until 2007 and predicted to reach 3.4 million tonnes in 2020. The objective of this study was to produce bioplastic from mango leaves. Mango trees are widely available in Malaysia and not fully utilized. In this project, the cellulose was extracted from the mango leaves through oxidation and bleaching. Then, the extracted cellulose was used in the production of bioplastic by using solution casting. The results showed that the lignocellulose content of our mango leaves were 29.6 % lignin, 33.9 % cellulose and 36.5 % hemicellulose. The bioplastic from mango leaves cellulose has shown good flexibility and strength as well as good opacity. In conclusion, bioplastic from mango leaves research was successfully prepared and can be developed as plastic bag or food packaging.